Mortality and vertebral fracture risk associated with long-term oral steroid use in patients with chronic obstructive pulmonary disease: A systemic review and meta-analysis. (1st April 2019) - Chang, Yu-Ping; Lai, Chien-Hao; Lin, Chiung-Yu; Chang, Ya-Chun; Lin, Meng-Chih; Chong, Inn-Wen; Sheu, Chau-Chyun; Wei, Yu-Feng; Chu, Kuo-An; Tsai, Jong-Rung; Lee, Cheng-Hung; Chen, Yung-Che
Short-term oral steroid use may improve lung function and respiratory symptoms in patients with stable chronic obstructive pulmonary disease (COPD). However, long-term oral steroid (LTOS) use is not recommended owing to its potential adverse effects. Our study aimed to investigate whether chronic use of oral steroids for more than 4 months would increase mortality and vertebral fracture risk in patients with stable COPD. A systemic search of the PubMed database was conducted, and meta-analysis was performed using Review Manager 5.3. Five studies with a total of 1795 patients showed there was an increased risk of mortality in patients using LTOS (relative risk, 1.63; 95% confidence interval (CI), 1.19–2.23; p < 0.0001; I 2 = 86%). In addition, four studies with a total of 17, 764 patients showed there was an increased risk of vertebral fracture in patients using LTOS (odds ratio, 2.31; 95% CI, 1.52–3.50; p = 0.03; I 2 = 65%). Our meta-analysis showed LTOS was associated with increased mortality and vertebral fracture risk in patients with COPD, and this risk may be due to the adverse effects of LTOS and progression COPD.